A contribution to the family Lecideaceae s. lat. (Lecanoromycetidae inc. sed., lichenized Ascomycota) in the southern subpolar region; including eight new species and some revised generic circumscriptions. (12th May 2014) - FRYDAY, Alan M.; HERTEL, Hannes
Abstract: Eight new species of Lecideaceae are described from the southern subpolar region: Bryobilimbia coppinsiana Fryday, a saxicolous species with one septate ascospores (Campbell Island, New Zealand); Immersaria fuliginosa Fryday, with a thallus composed of thalloconidia (Falkland Islands); Lecidea aurantia Fryday, with an orange thallus (Auckland Islands, New Zealand); L. campbellensis Fryday, with an endolithic thallus and apothecia resembling those of a species of Porpidia (Campbell Island); Poeltiaria ochyrae Hertel, which is similar to P. subincongua but with a thick areolate thallus (South Orkney and South Shetland Islands); P. tasmanica Fryday, which is similar to P. urbanskyana but with smaller ascopores (Tasmania); Poeltidea inspersa Fryday with an enolithic thallus and a hymenium with large oil globules (Falkland Islands); and Porpidia vulcanoides Hertel & Fryday with immersed apothecia with a thick margin and large ascospores (SW Chile). Lecidea kalbii Hertel is resurrected from the synonymy of L. mannii Tuck. and treated as a distinct species. The circumscription of genera within the Lecideaceae is also discussed: Poeltiaria is shown to be heterogeneous, and the genera Labyrintha and Notolecidea are reduced to synonymy with Poeltidea and Poeltiaria respectively, and the new combinations Poeltidia implexa (Malcolm et al .) Hertel & Fryday and Poeltiaria subcontinua (Hertel) Hertel & Fryday made. A key to the genera of Lecideaceae s. lat. is provided.